Abnormal shadow on chest radiograph: a supra – or infradiaphragmatic finding? - Katarzyna Biernacka-Racicot; Maciej Łukaszewski; Michał Nowański; Beata Socha; Piotr Grzelak (Wiedza Medyczna, 2021)
Incidental findings on chest X-ray of oncological patients need further evaluation in contrast-enhanced computed tomography (CT). We report two cases of abnormal shadows, detected on radiograph, in patients with breast cancer: the first one projected under the left hemidiaphragm and the second one obscuring the right hemidiaphragm. Both patients were asymptomatic, subjected to a surgery and to a CT. The first scan revealed a 15 mm diameter nodule in left lung with smooth margins and central calcifications. Whereas, the second exam showed a subcapsular, ring, calcified lesion in the liver. In both cases, CT was essential for staging and therapeutic choice.